Foreign aid, instability and governance in Africa - Simplice Asongu; Joseph Nnanna (African Governance and Development Institute (AGDI), 2019)
This study contributes to the attendant literature by bundling governance dynamics and focusing on foreign aid instability instead of foreign aid. We assess the role of foreign aid instabilit y on governance dynamics in fifty three African countries for the period 1996-2010. An autoregressive endogeneity-robust Generalized Method of Moments is employed. Instabilities are measured in terms of variance of the errors and standard deviations. Three main aid indicators are used, namely: total aid, aid from multilateral donors and bilateral aid. Principal Component Analysis is used to bundle governance indicators, namely: political governance (voice & accountability a nd political stability/no violence), economic governance (regulation quality and government effectiveness), institutional governance (rule of law and corruption-control) and general governance (political, economic and institutional governance). Our findings show that foreign aid instability increases governance standards, especially political and general governance. Poli cy implications are discussed.
Keywords: C53; F35; F47; O11; O55; 330; Instability; Foreign aid; Governance; Development; Africa